2017
DOI: 10.1139/cjb-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GFP-tagging on nitrogen fixation and plant growth promotion of an endophytic diazotrophic strain ofPaenibacillus polymyxa

Abstract: Green fluorescent protein (GFP), a renowned marker protein, is typically believed to be inert in affecting the physiology of host bacteria. We analyzed the effects of GFP-tagging on the ability of an endophytic diazotroph, Paenibacillus polymyxa P2b-2R, to fix nitrogen and promote overall growth of corn plants. The growth response and the amount of nitrogen fixed by P2b-2Rgfp-inoculated plants were compared with uninoculated controls and P2b-2R-inoculated plants at three harvests. P2b-2Rgfp inoculation signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…This is in line with previous studies conducted on endophytes in mangrove plants found in Saudi Arabia that revealed the most dominant species being Bacillus [13]. Bacillus and related species have also shown presence of proteases, pectinases and cellulases in endophytic bacteria of Paenibacillus polymyxa [22]. The survival of these endophytes is attributed to their ability to utilize these cellulose and pectin in the plant tissues [22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with previous studies conducted on endophytes in mangrove plants found in Saudi Arabia that revealed the most dominant species being Bacillus [13]. Bacillus and related species have also shown presence of proteases, pectinases and cellulases in endophytic bacteria of Paenibacillus polymyxa [22]. The survival of these endophytes is attributed to their ability to utilize these cellulose and pectin in the plant tissues [22].…”
Section: Discussionsupporting
confidence: 90%
“…Bacillus and related species have also shown presence of proteases, pectinases and cellulases in endophytic bacteria of Paenibacillus polymyxa [22]. The survival of these endophytes is attributed to their ability to utilize these cellulose and pectin in the plant tissues [22]. The other dominant bacterial endophytes included the Streptomyces which was dominantly found in the leaves of Xylocarpus granatum plant.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of these abilities in vitro after GFP-tagging were reported previously in Azospirillum brasilense [124]. A plausible reason for increased N fixing and plant growth-promoting efficacy of P2b-2R after GFP tagging could be the overexpression of structural nif genes (nifH, nifD, and nifK), which play an important role in the N-fixation process [121]. However, it is still unclear how GFP tagging affects the expression of structural nif genes of strain P2b-2R.…”
Section: Recent Studies Highlighting the Role Of Endophytic Diazotropmentioning
confidence: 53%
“…They tested this hypothesis by inoculating strain P2b-2R into agriculturally important crops, namely corn, canola, and tomato, and found that P2b-2R was able to colonize internal tissues of these crop species, fix substantial amounts of atmospheric N, and increase seedling length and biomass (see Table 2) [117][118][119]. These reports indicate the ability of strain P2b-2R to symbiotically associate with a broad range of hosts and promote their growth primarily by fixing atmospheric N. An interesting observation with the GFP-tagged P2b-2R strain (P2b-2Rgfp) was reported recently where P2b-2Rgfp inoculation significantly enhanced corn and canola seedling length and biomass as compared to the wild-type P2b-2R inoculation [119][120][121][122]. In addition, strain P2b-2Rgfp fixed significantly higher amounts of N as compared to the wildtype strain.…”
Section: Recent Studies Highlighting the Role Of Endophytic Diazotropmentioning
confidence: 61%
“…In fact, the endophyte Pseudomonas putida W619 presented a negative effect on poplar plants health and growth when GFP-labelled (Weyens et al, 2012). However, both the wild type and the GFP-tagged mutant of the diazotroph Paenibacillus polymyxa P2b-2R were able to promote the growth of pine (Tang et al, 2017), canola (Padda et al, 2016), and maize (Padda et al, 2017). In our work, a maize seed germination test was performed to ensure that the transformation did not affect the (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%